Empowering plant epigenetics to breed resilience of crops: From nucleolar dominance to transgenerational epigenetic inheritance - Zengjian Jeffrey Chen (The Plant Genome)
Abstract Advancements in genomic and epigenetic research in both plants and animals have transformed breeding methods and biotechnological strategies for crop improvement, particularly in the face of extreme weather challenges. These breakthroughs in plant biology and agriculture have laid a strong foundation for ensuring food security, promoting environmental sustainability, enhancing nutritional health, and driving basic science advances, as exemplified by Mendel's discovery of genetic principles and McClintock's discovery of transposable elements. Plant epigenetics has held a transformative potential for developing high‐yielding and resilient crops. In this review, I will examine various relevant epigenetic phenomena, including nucleolar dominance, paramutation, imprinting, somaclonal variation, and transgenerational epigenetic inheritance, to explore strategies for overcoming yield limitations in an increasingly volatile climate. This perspective aligns with the vision for plant breeding and sustainable agriculture championed by the late Professor Ronald L. Phillips.